Changing collective action: Norm-nudges and team decisions / Florian Diekert, Tillmann Eymess - Florian Diekert; Tillmann Eymess (University of Heidelberg, Department of Economics, 2021)
We test whether a descriptive norm-nudge is a suitable policy tool to increase cooperation in a social dilemma when decisions are taken by teams, not individuals. 10 Each team in our experiment comes from a different fishing boat at Lake Victoria, Tanzania. The provision of a norm-nudge is randomized across two decision making mechanisms, enabling us to identify experience with egalitarian or hierarchical decision structures, both present at Lake Victoria. The descriptive norm-nudge increases cooperation by 14 and 16 percentage points for egalitarian and hierarchical 15 team decisions, respectively. Captains from boats with hierarchical organization are particularly responsive.
urn:nbn:de:bsz:16-heidok-311204
Keywords: C72; C92; D7; D91; Q22; 650; collective action; team decisions; norm-nudges; common pool resources